FREQUENCY DEPENDENCE ON WATER TREE DEGRADATION IN XLPE MEDIUM VOLTAGE POWER CABLE - ,, NOOR HUSSAIN (2014)
Cross-linked polyethylene (XLPE) medium voltage (MV) power cables are being utilized worldwide due to their suitable electrical and physical characteristics. Water tree degradation is categorized as a pre-breakdown aging phenomena, it is associated with XLPE MV power cable insulation failure. Water treeing in cable insulation behaves with a nonlinear dielectric response. The purpose of this research is to diagnose water tree induced degradation in XLPE MV power cable insulation.